Two new whiprays, Maculabatis arabica sp. nov. and M. bineeshi sp. nov. (Myliobatiformes: Dasyatidae), from the northern Indian Ocean - Manjaji-Matsumoto, B. Mabel; Last, Peter R. (Zootaxa, 2016)
Two new medium-sized whiprays, Maculabatis arabica sp. nov. and M. bineeshi sp. nov., are described from specimens collected in coastal habitats of the northern Indian Ocean, off India and Pakistan. Both species superficially resemble M. randalli (Last, Manjaji-Matsumoto & Moore), and appear to have been confused with a more widely distributed whipray M. gerrardi Gray, and another undescribed species from the Indian Ocean. Maculabatis arabica sp. nov. (attains at least 63 cm DW) is diagnosed by a combination of external characters, i.e. morphometrics (e.g. relatively short disc, narrow interspaces between paired structures on the head), squamation (relatively slow denticle development and a characteristic denticle band shape), plain dorsal disc coloration (rather than spotted), and tail light brown and banded beyond the caudal sting in juveniles but almost plain in adults. Maculabatis bineeshi sp. nov. (attains at least 66 cm DW) is diagnosed by a combination of characters, i.e. morphometrics (e.g. suboval to weakly rhombic disc in young), squamation (rapid denticle development and broad denticle band with margins truncate near pectoral-fin insertions), plain dorsal disc coloration (no white spots), and a dark blackish tail (especially in young) with weakly mottled banding on its dorsal surface beyond the caudal sting. Maculabatis arabica sp. nov. appears to be confined to the Arabian Sea (from Pakistan to western India), whereas M. bineeshi sp. nov. occurs in the Arabian Sea (off Pakistan and northwestern India) and in the Bay of Bengal (confirmed off Odisha, eastern India).